The Genesis and Development of the Maqāṣid al-Qur’ān (American Journal of Islam and Society, 2013)
Maqāṣid al-Qur’ān is an emerging science that promotes an understanding of the Qur’anic discourse’s purposive (maqasidic) angle. Beginning with preliminary ideas in the fifth Islamic century, it has now achieved the status, in the eyes of many prominent contemporary Muslims, of being a specific science. Having been the subject of scholarly discussion in articles, books, television programs, seminars and conferences, this subject has created a new academic debate in the very contemporary field of Qur’anic studies. This study explores its genesis and conceptual developments over time by analyzing the root of this science as well as how it has fared at the hands of early and modern scholarship of the Qur’an. Its findings are expected to contribute to presenting this field to the public in a compact form.